Green Economy and Environmental Innovation Strategies: A Review of the Literature - Maharani Putri Rabbani; Sofie Yunida Putri; Maheran Zakaria (Journal of Economics Development Issues, 2023)
The research places a strong emphasis on the influence of stakeholder theory in shaping strategies for eco-innovation, while also highlighting the pivotal role of technological innovation and well-crafted environmental policies in driving the advancement of green growth. Additionally, the studies recognized the significance of regional context and the necessity for tailored approaches to facilitate a comprehensive transition towards a green economy. Furthermore, the study's literature review delves comprehensively into the existing body of knowledge and research at the juncture of the green economy and green technology. It offers a comprehensive overview of the scholarly landscape by bringing attention to key themes and emerging trends across various disciplines. Overall, the collective findings of the research consistently underscore the paramount importance of both the green economy and innovations in green technology in the pursuit of sustainable development.